The impact of diversity on innovation in countries - Beckhauser, Sheila Patrícia Ramos; Gomes, Giancarlo (Revista de Administração da UFSM, 2019)
The objective of the study was to identify the factors of diversity that influence innovation in countries. For that, a quantitative methodology was adopted regarding the approach, being descriptive regarding the objectives. The multivariate statistical technique used for data analysis was multiple linear regression. The sample was composed of 127 countries from secondary data, extracted from the indexes: World Economic Forum and Social Progress Imperative. The results showed that among the eleven variables of the diversity used in the study analysis, six variables had an impact on the innovation of the countries, which are: women’s study years, education inequality, homosexual tolerance, freedom over life decisions, religious tolerance and discrimination and violence against minorities. Although it is not yet possible to generalize conclusions from the results found, being that a limitation of the present study, it has also showed that there are indeed implications between innovation and aspects of diversity.